Development of SMART-Based Soft Skills: Integration of STEM, HOTS Based on Project-Based Learning for Vocational Students - Muhammad Furqon; Aris Riyanto; Idris, Iswandi; Muhammad Furqon (CV. Media Digital Publikasi Indonesia, 2025)
The 21st-century workforce requires a strong foundation in both technical and soft skills, particularly in vocational education. This study investigates the development of soft skills among vocational students through the SMART model, integrating STEM (Science, Technology, Engineering, and Mathematics) and HOTS (High Order Thinking Skills) within a project-based learning (PBL) framework. The aim is to foster critical soft skills, such as problem-solving, collaboration, and communication, essential for adapting to the ever-evolving demands of the modern workforce. The study explores the impact of this integrative approach and assesses students' progress through a series of technical projects. Preliminary findings suggest that the SMART model can significantly enhance students' preparedness for the workforce, equipping them with the necessary skills to thrive in complex and dynamic environments.